Vew Educational Program Master “Voice Self-service Systems” - Рыбин, Сергей Витальевич; Матвеев, Юрий Николаевич; Кабаров, Владимир Иосифович (Computer Tools in Education, 2017)
This article deals with the development and implementation at the ITMO University a new educational practice-oriented master’s program "Voice Self-service Systems". The program aims to train specialists in innovative products for contact centers.The unique  of conditions of implementation of the program is that students will be able to gain real practical experience along the entire chain of development, implementation, maintenance and operation of the innovative products developed by Speech Technology Center Ltd. - one of the world’s leading developers in the field of high-quality recording, processing and analysis of audio and video data, speech synthesis and recognition.
Keywords: voice self-service system; call-center; speech recognition and synthesis; speech analytics; biometric authentication